Dislocation rate after hip arthroplasty due to metastatic bone disease: a retrospective cohort study evaluating the postoperative dislocation risk across different articulating solutions - Afrim Iljazi; Michala Skovlund Sørensen; Thea Hovgaard Ladegaard; Søren Overgaard; Michael Mørk Petersen (Acta Orthopaedica, 2023)
Background and purpose: Joint stability after hip replacement (HR) in patients with metastatic bone disease (MBD) is of special importance. Dislocation is the second leading cause of implant revision in HR, while survival after MBD surgery is poor with an expected 1-year survival of around 40%. As few studies have investigated the dislocation risk across different articulation solutions in MBD, we conducted a retrospective study on primary HR for patients with MBD treated in our department. Patients and methods: The primary outcome is the 1-year cumulative incidence of dislocation. We included patients with MBD who received HR at our department in 2003–2019. We excluded patients with partial pelvic reconstruction, total femoral replacement, and revision surgery. We assessed the incidence of dislocation with competing risk analysis with death and implant removal as competing risks. Results: We included 471 patients. Median follow-up was 6.5 months. The patients received 248 regular total hip arthroplasties (THAs), 117 hemiarthroplasties, 70 constrained liners, and 36 dual mobility liners. Major bone resection (MBR), defined as resection below the lesser trochanter, was performed in 63%. The overall 1-year cumulative incidence of dislocation was 6.2% (95% CI 4.0–8.3). Dislocation stratified by articulating surface was 6.9% (CI 3.7–10) for regular THA, 6.8% (CI 2.3–11) for hemiarthroplasty, 2.9% (CI 0.0–6.8) for constrained liner, and 5.6% (CI 0.0–13) for dual mobility liners. There was no significant difference between patients with and without MBR (p = 0.5). Conclusion: The 1-year cumulative incidence of dislocation is 6.2% in patients with MBD. Further studies are needed to determine any real benefits of specific articulations on the risk of postoperative dislocation in patients with MBD.